Breastfeeding Contributes to Physiological Immune Programming in the Newborn - Camacho-Morales, Alberto; Caba, Mario; García-Juárez, Martín; Caba-Flores, Mario Daniel; Viveros-Contreras, Rubí; Martínez-Valenzuela, Carmen (Frontiers in Pediatrics, 2021)
The first 1000 days in the life of a human being are a vulnerable stage where early stimuli may program adverse health outcomes in future life. Proper maternal nutrition before and during pregnancy modulates the development of the fetus, a physiological process known as fetal programming. Defective programming promotes non-communicable chronic diseases in the newborn which might be prevented by postnatal interventions such as breastfeeding. Breast milk provides distinct bioactive molecules that contribute to immune maturation, organ development, and healthy microbial gut colonization, and also secures a proper immunological response that protects against infection and inflammation in the newborn. The gut microbiome provides the most critical immune microbial stimulation in the newborn in early life, allowing a well-trained immune system and efficient metabolic settings in healthy subjects. Conversely, negative fetal programming by exposing mothers to diets rich in fat and sugar has profound effects on breast milk composition and alters immune profiles in the newborn. At this new stage, newborns become vulnerable to immune compromise, favoring susceptibility to defective microbial gut colonization and immune response. This review will focus on the importance of breastfeeding and its immunological biocomponents that allow physiological immune programming in the newborn. We will highlight the importance of immunological settings by breastfeeding, allowing proper microbial gut colonization in the newborn as a window of opportunity to secure effective immunological response.